3 Eps 3 Cadmium Talk Quality assurance in laboratory testing for Cd in cacao soil and tissue - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2025)
Moderator: Althea McKenzie. Speakers: Jesse Dekeyrel, Ruth Quiroga and Deisy Toloza Moreno